Interactions of the hepatitis C virus protease inhibitor faldaprevir with cytochrome P450 enzymes: In vitro and in vivo correlation. (14th January 2015) - Sabo, John P.; Kort, Jens; Ballow, Charles; Kashuba, Angela D.M.; Haschke, Manuel; Battegay, Manuel; Girlich, Birgit; Ting, Naitee; Lang, Benjamin; Zhang, Wei; Cooper, Curtis; O'Brien, Drané; et al.
Abstract The potential inhibition of the major human cytochrome P450 (CYP) enzymes by faldaprevir was evaluated both in vitro and in clinical studies (healthy volunteers and hepatitis C virus [HCV] genotype 1‐infected patients). In vitro studies indicated that faldaprevir inhibited CYP2B6, CYP2C9, and CYP3A, and was a weak‐to‐moderate inactivator of CYP3A4. Faldaprevir 240 mg twice daily in healthy volunteers demonstrated moderate inhibition of hepatic and intestinal CYP3A (oral midazolam: 2.96‐fold increase in AUC0–24 h), weak inhibition of hepatic CYP3A (intravenous midazolam: 1.56‐fold increase in AUC0–24 h), weak inhibition of CYP2C9 ([S]‐warfarin: 1.29‐fold increase in AUC0–120 h), and had no relevant effects on CYP1A2, CYP2B6, or CYP2D6. Faldaprevir 120 mg once daily in HCV‐infected patients demonstrated weak inhibition of hepatic and intestinal CYP3A (oral midazolam: 1.52‐fold increase in AUC0–∞), and had no relevant effects on CYP2C9 or CYP1A2. In vitro drug‐drug interaction predictions based on inhibitor concentration ([I])/inhibition constant (Ki) ratios tended to overestimate clinical effects and a net‐effect model provided a more accurate approach. These studies suggest that faldaprevir shows a dose‐dependent inhibition of CYP3A and CYP2C9, and does not induce CYP isoforms.